Peran Literasi Bisnis Digital dalam Menumbuhkan Jiwa Kewirausahaan pada Remaja - Triatmi Puji Hastuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
Information technology has rapidly brought progress and great influence on human life. Digitalization facilitates all the needs and affairs of modern humans, because almost everything can be controlled with a smartphone. The purpose of this study is to determine the role of digital business literacy in fostering entrepreneurial spirit in adolescents. This research uses a qualitative method that focuses on analyzing the role of digital business literacy. This research provides an overview of the role of digital business literacy in fostering the entrepreneurial spirit in adolescents. The results of the discussion of several previous researchers, it can be concluded that the socialization of digital business literacy is proven to have a positive and significant influence in fostering the entrepreneurial spirit in adolescents / generation Z. The largest number of entrepreneurs is the age group of the entrepreneurial spirit. The largest number of entrepreneurs is the age group over 50 years, but digital entrepreneurs are currently dominated by young entrepreneurs. This is in accordance with the digital literacy theory proposed by Paul Gilbert, that digital literacy is able to make a person think critically, not just technical skills.